Microbial metabolite deoxycholic acid controls Clostridium perfringens-induced chicken necrotic enteritis through attenuating inflammatory cyclooxygenase signaling - Wang, Hong (Sci Rep, 2019)
Necrotic enteritis (NE) caused by Clostridium perfringens infection has reemerged as a prevalent poultry disease worldwide due to reduced usage of prophylactic antibiotics under consumer preferences and regulatory pressures. The lack of alternative antimicrobial strategies to control this disease is mainly due to limited insight into the relationship between NE pathogenesis, microbiome, and host responses. Here we showed that the microbial metabolic byproduct of secondary bile acid deoxycholic acid (DCA), at as low as 50 µM, inhibited 82.8% of C. perfringens growth in Tryptic Soy Broth (P < 0.05). Sequential Eimeria maxima and C. perfringens challenges significantly induced NE, severe intestinal inflammation, and body weight (BW) loss in broiler chickens. These negative effects were diminished (P < 0.05) by 1.5 g/kg DCA diet. At the cellular level, DCA alleviated NE-associated ileal epithelial death and significantly reduced lamina propria cell apoptosis. Interestingly, DCA reduced C. perfringens invasion into ileum (P < 0.05) without altering the bacterial ileal luminal colonization. Molecular analysis showed that DCA significantly reduced inflammatory mediators of Infγ, Litaf, Il1β, and Mmp9 mRNA accumulation in ileal tissue. Mechanism studies revealed that C. perfringens induced (P < 0.05) elevated expression of inflammatory mediators of Infγ, Litaf, and Ptgs2 (Cyclooxygenases-2 (COX-2) gene) in chicken splenocytes. Inhibiting the COX signaling by aspirin significantly attenuated INFγ-induced inflammatory response in the splenocytes. Consistent with the in vitro assay, chickens fed 0.12 g/kg aspirin diet protected the birds against NE-induced BW loss, ileal inflammation, and intestinal cell apoptosis. In conclusion, microbial metabolic product DCA prevents NE-induced BW loss and ileal inflammation through attenuating inflammatory response. These novel findings of microbiome protecting birds against NE provide new options on developing next generation antimicrobial alternatives against NE.